2018
DOI: 10.1101/467597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germline deletion reveals a non-essential role of the atypical MAPK6/ERK3

Abstract: words) 24MAPK6/ERK3 is an atypical member of the MAPKs. An essential role has been suggested by the 25 perinatal lethal phenotype of ERK3 knockout mice carrying a lacZ insertion in exon 2 due to 26 pulmonary disfunction and by defects in function, activation and positive selection of T cells. To 27 study the role of ERK3 in vivo, we generated mice carrying a conditional Erk3 allele with exon3 28 flanked by LoxP sites. Loss of ERK3 protein was validated after deletion of Erk3 in the female 29 germ line using zo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…These mice were generated by inserting LacZ into exon 2. A more recent study using a conditional knockout where exon 3 of ERK3 was flanked by loxP observed that germline deletion of ERK3 resulted in ERK3-deficient mice that were viable (80).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…These mice were generated by inserting LacZ into exon 2. A more recent study using a conditional knockout where exon 3 of ERK3 was flanked by loxP observed that germline deletion of ERK3 resulted in ERK3-deficient mice that were viable (80).…”
Section: Limitations Of the Studymentioning
confidence: 99%